2019
DOI: 10.18203/2349-3291.ijcp20192000
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of neonates with acute renal injury in neonatal intensive care unit at GMERS Medical College and General Hospital, Gotri, Vadodara, Gujarat, India

Abstract: Background: Acute kidney injury (AKI) is defined as an acute deterioration in ability of the kidneys to maintain homeostasis of body fluids and electrolytes leading to retention of wasted and toxic metabolic end products. It is fairly common in newborn population and is a major contributor of neonatal mortality and morbidity. The aim was to study the incidence of renal failure in high risk neonates and risk factors for renal failure.Methods: A prospective observational study was done to evaluate renal profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…14 In a retrospective study done by Bolat et al including 162 babies with AKI, it was found that 38% of the neonates had respiratory distress syndrome. 15 In a prospective study done by Timovska et al it was found that amongst 50 babies with AKI, 24% had respiratory distress syndrome. 10 In a case control study done by El Badawy et al including 41 neonates, it was found that 70.5% of the babies had exposure to nephrotoxic drugs.…”
Section: Studymentioning
confidence: 99%
“…14 In a retrospective study done by Bolat et al including 162 babies with AKI, it was found that 38% of the neonates had respiratory distress syndrome. 15 In a prospective study done by Timovska et al it was found that amongst 50 babies with AKI, 24% had respiratory distress syndrome. 10 In a case control study done by El Badawy et al including 41 neonates, it was found that 70.5% of the babies had exposure to nephrotoxic drugs.…”
Section: Studymentioning
confidence: 99%
“…Due to lack of precise definition, the real prevalence of AKI in the neonate is unknown, and varies from 1.5% to 56%, associated with higher mortality and consuming more expenses due to long hospital stay [4][5][6][7] . In India, AKI incidence ranges from 4.2% to 37.1%, with a 60% mortality in neonates [8][9][10] . Presence of shock, sepsis, use of mechanical ventilation and need of renal replacement therapy were associated with higher mortality in neonates with AKI [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%